EFFECT OF BIOAGENTS ON SPORE GERMINATION OF ALTERNARIA BURNSII - SUNIL KUMAR PIPLIWAL; K. B. JADEJA; ANSHUL SHARMA; JITENDRA KUMAR DHAKAD (The Bioscan, 2015)
The effect of cultural filtrate of Trichoderma and Pseudomonas fluorescens isolates on spore germination of A. burnsii. The cultural filtrate of Trichoderma viz. Trichoderma isolate-11 and Trichoderma isolate-19 were found most effective and spore germination inhibition were 63.98 per cent and 63.30 per cent against A. burnsii, respectively. Among culture filtrate of P. fluorescens viz. P. Fluorescens isolate-7 and P. fluorescens isolate-2 were highly effective in the reduction of spore germination of A. burnsii. Which were inhibited spore germination 59.32 per cent with P. fluorescens isolate-7 and 52.92 per cent with P. fluorescens isolate-2 against A. burnsii.